Molecular evidence of a putative new Atractolytocestus Anthony, 1958 (Cestoda: Caryophyllidea) species parasitic on common carp (Cyprinus carpio) in the People's Republic of China. (17th December 2021) - Fu, P.P.; Li, W.X.; Cheng, Y.Y.; Zou, H.; Wu, S.G.; Li, M.; Wang, G.T.
Abstract: Three tapeworm species belonging to the genus Atractolytocestus Anthony, 1958 (Cestoda: Caryophyllidea) were reported from the common carp, Cyprinus carpio L., 1758 in the People's Republic of China so far: Atractolytocestus sagittatus ; Atractolytocestus tenuicollis ; and Atractolytocestus huronensis . In this study, we identified a putatively new tapeworm species in common carp from the Danjiangkou Reservoir in Central China (Hubei Province). The species is morphologically similar to A . sagittatus, but it differed conspicuously in sequences of three molecular markers. Ribosomal internal transcribed spacers 2 sequence identity of the new species was 94.7–95.5%, 91.8–92.7% and 80.0–83.9% with A . huronensis, A . tenuicollis and A . sagittatus, respectively. cytochrome c oxidase and NADH dehydrogenase subunit 3 sequence identity with these three species was lower than 92%. We conclude that this is a new tapeworm species, and we named it after the locality: Atractolytocestus danjiangkouensis n. sp.